Juridical Analysis of Regional Asset Management to Increase Regional Original Revenue; Case Study in Bandung Regency - Ita Susanti; Sumiyati Sumiyati; Mia Rosmiati (Universitas Muhammadiyah Ponorogo, 2022)
The concept of the welfare state of the Republic of Indonesia as stated in the Preamble to the 1945 Constitution, its implementation is realized in the form of regional government (decentralization), both provincial, city and district governments. Each local government has the right and obligation to take care of its administration to improve efficiency and effectiveness. After the Covid-19 Pandemic, almost all local governments experienced a decline in obtaining regional original revenue. The same thing happened to the local government of Bandung Regency, after the Covid-19 Pandemic, economic growth has stagnated for almost 2 years. This causes the regional original revenue of Bandung Regency to decrease. In addition, the decline is because not all regional potentials have been explored and managed properly. The research was conducted in three stages. The first stage, the literature study, is an inventory of regulations regarding the management of regional property/regional assets and regulations regarding regional original revenue. The second stage is observation at several related institutions. The third stage is the discussion by comparing the normative juridical legal arrangements regarding the management of regional assets (das sollen) and their application in reality (das sein). The results show that the Bandung Regency Government has implemented regional asset management based on the asset management cycle which is under the responsibility of the Regional Finance and Assets Agency. In addition to the asset cycle, regional asset management is also carried out according to regulations. Asset management in accordance with the asset management cycle and the laws and regulations can certainly significantly increase the regional original revenue of Bandung Regency. One of the efforts made by the Bandung Regency Government in increasing its regional revenue is improving road access to tourist destinations. With infrastructure improvements, it is hoped that it can become a special attraction for tourists visiting tourist destinations in Bandung Regency